Evaluation of recurrence of periodontal disease after treatment in obese and normal weight patients: Two-year follow-up - Zuza, Elizangela C.; Pires, Juliana R.; Almeida, Ana Alice de; Toledo, Benedicto E. C. [UNESP]; Guimaraes-Stabili, Morgana R. [UNESP]; Rossa Junior, Carlos [UNESP]; Barroso, Eliane M. (Wiley-Blackwell, 2020)
Background Obesity may represent a chronic low-grade inflammation, but there is a lack of long-term longitudinal studies. The aim of this longitudinal study was to evaluate the recurrence of periodontal disease in obese and normal weight patients submitted to scaling and root planing. Methods The study included 22 patients who had received periodontal treatment 2 years previously, 13 obese and nine non-obese. The patients were evaluated for anthropometric measurements of body mass index, waist circumference, waist-to-hip ratio, and fat percentage through bioimpedance. The following periodontal parameters were recorded: visible plaque index (VPI), gingival bleeding index (GBI), probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP). The immunological evaluation analyzed the proinflammatory cytokines interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-alpha) in the gingival crevicular fluid (GCF). Results Obese and normal weight patients did not differ in relation to the periodontal parameters of VPI, GBI, PD, CAL, or BOP 2 years after completion of the periodontal therapy. Sites with periodontitis in obese individuals showed higher levels of IL-6 and TNF-alpha in the gingival fluid (P <0.05). Conclusion Obese and normal weight individuals had similar periodontal behaviors, with low recurrence of the periodontal disease; however, obesity was related to increased inflammatory activity in gingival fluid, which may become a risk indicator for future greater recurrence of the disease in the presence of inadequate plaque control.
Keywords: body weight; gingival crevicular fluid; inflammation; obesity; periodontal diseases